Alpinia calcarata Roscoe: A potential phytopharmacological source of natural medicine - Rahman, Md Atiar; Islam, Md Shahidul (Pharmacognosy Reviews)
Alpinia calcarata Roscoe (Family: Zingiberaceae), is a rhizomatous perennial herb, which is commonly used in the traditional medicinal systems in Sri Lanka. Alpinia calcarata is cultivated in tropical countries, including Sri Lanka, India, and Malaysia. Experimentally, rhizomes of Alpinia calcarata are shown to possess antibacterial, antifungal, anthelmintic, antinociceptive, anti‑inflammatory, antioxidant, aphrodisiac, gastroprotective, and antidiabetic activities. Phytochemical screening revealed the presence of polyphenols, tannins, flavonoids, steroid glycosides and alkaloids in the extract and essential oil of this plant. Essential oil and extracts from this plant have been found to possess wide range of pharmacological and biological activities. This article provides a comprehensive review of its ethnomedical uses, chemical constituents and the pharmacological profile as a medicinal plant. Particular attention has been given to the pharmacological effects of the essential oil of Alpinia calcarata in this review so that the potential use of this plant either in pharmaceutics or as an agricultural resource can be evaluated.
Keywords: Alpinia calcarata; essential oil; hot alcoholic extract; pharmacological; phytochemical